2003
DOI: 10.1021/bi020658k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Sequence-Specific Recognition of ssDNA by an Autoantibody

Abstract: 11F8 is a pathogenic monoclonal anti-ssDNA autoantibody isolated from a lupus prone mouse. Previous studies established that 11F8 is sequence-specific and identified the thermodynamic and kinetic basis for the specific recognition of ssDNA, and binding site mutations of a single-chain construct reveal that (Y32)LCDR1, (R31)HCDR1, (W33)HCDR1, (R98)HCDR3, (L97)HCDR3, and (Y100)HCDR3 are responsible for approximately 80% of the binding free energy. Here we evaluate the role of these residues along with a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…These behaviors may be due to different biological requirements for fast binding and kinetic stability of each complex. Our results contribute to the search for a consensus view of sequence readout in the kinetics of protein binding to double-and single-stranded nucleic acids (40,41), equivalent to recent progress on the understanding of proteinprotein association (35,42).…”
Section: Discussionmentioning
confidence: 62%
“…These behaviors may be due to different biological requirements for fast binding and kinetic stability of each complex. Our results contribute to the search for a consensus view of sequence readout in the kinetics of protein binding to double-and single-stranded nucleic acids (40,41), equivalent to recent progress on the understanding of proteinprotein association (35,42).…”
Section: Discussionmentioning
confidence: 62%
“…The apparent association (k on ) and dissociation (k off ) rate constants were determined as previously described. 22,24 Briefly, the excitation wavelengths were the same as used for equilibrium experiments and the emission was monitored with suitable cutoff filters. All measurements were performed in 20 mM Tris-HCl, pH 8.0, 100 mM NaCl, 20% w/v sucrose at 58C.…”
Section: Stopped-flow Measurementsmentioning
confidence: 99%
“…19 Mutagenesis and structural studies suggest that R31 V H at the periphery of the binding site contacts 1 through both salt bridge and specific base contacts. 20,24,35 A binding site serine in place of arginine means loss of positive charge at the interface, eliminating potential hydrogen bond and electrostatic contacts with the DNA backbone. While direct side chain-base contacts could only be assessed through…”
mentioning
confidence: 99%
“…However, since antissDNA antibody has been shown in a limited number of experimental and clinical studies to be both hydrolytic and nephritogenic, it is suggested that it may serve as a strong flare predictor. [2][3][4] The important role of anti-ssDNA antibody is supported by studies in mouse models of nephritogenic lupus in which only anti-ssDNA antibodies were found 6,7 as well as by the findings of Swanson et al, 1 & Spatz et al, 8 that some anti-dsDNA human antibodies are not pathogenic at all. The ultimate goal of this study was to determine the optimal conditions for analysis of the types and activity of highly purified human antissDNA (IgG antibody) in order to gain deeper insight into functional characteristics such as binding, DNA hydrolysis, cytotoxicity and the role of these antibodies in SLE pathogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4] Consequently, the level of anti-DNA antibodies in patients' sera is used to monitor disease activity and progression. [3][4][5] It is still not quite clear which fractions between these two categories of anti-DNA autoantibodies are pathogenic and why.…”
Section: Introductionmentioning
confidence: 99%